Additional micromineral Mn and Cu in ration to rumen biofermentation activities of sheep in vitro method - Farida Fathul; Sitti Wajizah (Jurnal Ilmu Ternak dan Veteriner, 2010)
Ruminants need micro mineral for both their own requirements and rumen microbe activities. The objective of this research was to study the effect of Mn, Cu, and its combination addition in ration on the activity of in vitro fermentation using sheep rumen liquid. This research was conducted at Laboratory of Ruminant Nutrition Faculty of Animal Science Bogor Agricultural Institute. The rations were R0 = basal ration; R1 = basal ration + 40 ppm Mn; R2 = basal ration + 10 ppm Cu; dan R3 = basal ration + 40 ppm Mn + 10 ppm Cu. The result indicated that addition of Mn, Cu, or Mn+Cu did not significantly influence (P>0.05) pH, NH3, bacteria and VFA; but they significantly increased (P<0.01) dry matter digestibility (DMD) and organic matter digestibility (OMD). The average: pH was 4.78 ± 0.07 – 4.89 ± 0.06; NH3 was 6.77 ± 2.07 – 7.47±0,67 mM, and VFA was 93.19 ± 55.79 – 136.61±15.31 mM.  R1 gave the highest value of DMD (57.63%) and OMD (70.32%). The VFA related positively to NH3 (r = 0.86); with the equation Ý = -266.9 + 54.182 X and R2 = 0.74.  It was concluded that additional of Mn, Cu, or Mn+Cu did not alter pH, NH3, and VFA. The additional of Mn altered DMD, but additional of Mn+Cu reduced DMD and OMD. Key Words: pH, NH3, VFA, DMD, OMD